2-oxoglutarate regulates binding of hydroxylated hypoxia-inducible factor to prolyl hydroxylase domain 2 - Abboud, M; McAllister, T; Leung, I; Chowdhury, R; Jorgensen, C; Domene, C; Mecinović, J; Lippl, K; Hancock, R; Hopkinson, R; Kawamura, A; Claridge, T; et al. (Royal Society of Chemistry, 2018)
Prolyl hydroxylation of hypoxia inducible factor (HIF)-α, as catalysed by the Fe(II)/2-oxoglutarate (2OG)-dependent prolyl hydroxylase domain (PHD) enzymes, has a hypoxia sensing role in animals. We report that binding of prolyl-hydroxylated HIF-α to PHD2 is ~50 fold hindered by prior 2OG binding; thus, when 2OG is limiting, HIF-α degradation might be inhibited by PHD binding